Optimization of Integrated Management to use Surface Water and Groundwater Resources by Using Imperialist Competitive Algorithm and Genetic Algorithm (Tehran Plain) - Vahidreza Amiresmaeili; Hossein Jahantigh (Salehan Institute of Higher Education, 2017)
The extensive development of activities in different areas of surface and underground water resources and the lack of sufficient attention to integrated planning and management necessitates research in this regard. Due to the imbalance in the distribution of water resources and the constraints on water resources and the constraints on the use of surface water, it is necessary to combine the use of surface water and underground water resources. In this study, the modelling is done in such a way that maximum use of surface water is achieved and the rate of utilization of groundwater reaches its minimum. In this study, imperialist and genetic competition algorithms are used for optimization. In this study, the extent of utilization of groundwater resources is limited and it has tried to use all of the surface water resources of Tehran Plain. The results of this study showed that the amount of water needed from the beginning of the year begins to decrease and then increases, and this increase is related to the warm seasons of the year. Surface water levels increase in cold seasons. In the cold seasons, the supply of water requirements was complete, but in the warm seasons, some water requirements were not met. The results of this study indicate that if the amount of groundwater resources is kept to an optimum level within 10 years, the problem of groundwater resources in Tehran plain will be solved.